2009
DOI: 10.1542/peds.2007-3395
|View full text |Cite
|
Sign up to set email alerts
|

How Well Can Hospital Readmission Be Predicted in a Cohort of Hospitalized Children? A Retrospective, Multicenter Study

Abstract: Background-Children with complex chronic conditions depend upon both their families and systems of pediatric health care, social services, and financing. Investigations into the workings of this ecology of care would be advanced by more accurate methods of population-level predictions of the likelihood for future hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
115
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 34 publications
10
115
2
3
Order By: Relevance
“…Previous studies examining readmissions in children do not provide a detailed view of the dialysis population (6,7). Our objective was to examine hospital readmissions among a cohort of children receiving chronic dialysis to identify factors associated with higher rates of 30-day readmission in this vulnerable population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies examining readmissions in children do not provide a detailed view of the dialysis population (6,7). Our objective was to examine hospital readmissions among a cohort of children receiving chronic dialysis to identify factors associated with higher rates of 30-day readmission in this vulnerable population.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,6 Many children who experience high health care costs incur frequent hospital admissions and lengthy hospitalizations. [15][16][17][18] Previous studies have reported that hospital care accounts for as much as 80% of total health care spending in children with severe chronic conditions. 2,5,6 Spending on other health services, such as emergency department care, medications, and primary care, is much smaller.…”
mentioning
confidence: 99%
“…1 In pediatrics, readmissions within a year of an index admission are common and cost more than $1 billion annually. 2,3 As a result, development of a pediatric readmissions measure has been identified as a priority for national quality reporting programs. 4,5 Adult conditionspecific readmission rates for Medicare patients are already publicly reported online in Medicare' s national quality report.…”
mentioning
confidence: 99%